Returned to work employees: predictors of their well-being - Basiron, Balkis; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2022)
Due to fast changing working environment leading to potential strains among employees, chronic health problems (CHP) become more prevalent especially among aging employees regardless of working sectors. By 2019, Public Service Department (PSD) reported 4,677 public service employees (PSE) with CHP. The organization has suffered losses due to the long-term medical leave taken by the CHP PSE, particularly when it involves talents. Organization has to bear greater losses if they do not take into account the well-being of returned to work (RTW) employees. To date, there are unavailable studies conducted on well-being of RTW PSE with CHP in Malaysia. Therefore, this study aims to determine predictors of well-being among PSE with CHP after returning to work at Ministry of Health Malaysia (MOH) which focuses on three (3) predictors identified: work adjustment, work environment and perceived organizational support (POS). This study was conducted based on quantitative, non-experimental and cross-sectional research paradigm. Specifically, this study employed descriptive and correlational research designs to entertain the research objectives. Based on findings of data collected among 125 respondents, the most dominant predictor of well-being among RTW employees is work adjustment and followed by work environment. This study contributes significantly to the Theory of Work Adjustment and Job Demands-Resources Model. Recommendations for future research are also provided.